(untitled) (Research, Society and Development, 2021)
Analyze the spatial distribution of sociodemographic indicators with the Covid-19 pandemic, through an integrative review. An integrative literature review was carried out in the electronic libraries Pubmed, Web of Science, Medline and Lilacs, in November and December 2020, using descriptors indexed in the DECS / MeSH. The guiding question of the study was: “How did Brazilian social indicators evolve through the Covid-19 pandemic?”. Original studies, published in 2020, available in full, in Portuguese and English, were included. The results were presented in a synoptic table with the main information for each study. The publication sources included different journals. Twelve ecological studies and two exploratory-quantitative studies were identified. As for the place of performance, five searched for data from all Brazilian states, seven from the Northeast and three from the Southeast. The geographical behavior of the indicators with the pandemic in Brazil, were related to the pattern of spread of the disease, urban mobility and population density. Through the spatial analysis, it was observed that the states presented vulnerabilities and heterogeneous behavior of the sociodemographic indicators, which contributed to the high transmissibility of the virus, worsening of the cases and difficulty in adopting the measures of social isolation.